ANALISIS PRODUKTIVITAS PEGAWAI MENGGUNAKAN JARINGAN SARAF TIRUAN PROPAGASI BALIK - Riffa Haviani Laluma (STMIK Mardira Indonesia, Bandung, 2015)
Labor productivity is an integrated interaction between production employees by way of an agency. To the Staff motivation is important because the quality and productivity of labor will usually aroused when their impulses work, productivity assessment can be predicted by using the concept of Artificial Neural Network (ANN) where the encouragement of this work can be influenced by several factors such as ability, attitudes, behaviors that will serve as the input of neural networks to produce the level of productivity in the form of good or bad value. Keywords: employee productivity, artificial neural network